Solubility phase transition behavior of gold nanoparticles in colloidal solution - Yan, Hao (Kansas State University, 2009)
Nano-size materials are new materials in an intermediate state between the bulk and atomic or molecular states. Nanoparticles in colloidal solution and their assemblies have the great attention of researchers to investigate the novel fundamental properties and numerous applications. In this dissertation, we investigated the solubility phase transition behavior of gold nanoparticles in colloidal solution. We used the nearly monodisperse gold nanoparticles synthesized by either the inverse micelle or the solvated metal atom dispersion methods followed by digestive ripening. The gold nanoparticles were ligated with alkyl chains, which were dodecanethiol, decanethiol, or octanethiol for individual samples. They dispersed in toluene or t-butyl toluene like large molecules at room temperature. In analogy to molecular solutions, the colloidal solution had thermally reversible phase transitions between a dissolved phase of dispersed single nanoparticles and dispersed-aggregation co-existing phase. A more polar solvent, 2-butanone, was added to the colloidal solution for changing the solubility of gold nanoparticles and adjusting the phase transition temperatures to accessible temperatures. Superclusters formed by the nanoparticles when the colloidal solutions were quenched from a one-phase regime at high temperature to a two-phase regime at low temperature. Solubility phase diagrams were obtained for gold nanoparticles with different ligands in the mixtures of different ratios of 2-butanone and toluene or t-butyl toluene. The explanation from classical ideal solution theory gave the fusion enthalpy of superclusters. Temperature quenches from the one-phase to the two-phase regime yielded superclusters of the nanoparticle solid phase with sizes that depended on the quench depth. Classical nucleation theory was used to describe these sizes using a relative small value of the surface tension for the nanoparticle solid phase. This value is consistent with molecule size scaling of the surface tension. In total these results show that the solubility behavior of nanoparticles in colloidal solution is similar to the behavior in molecular solutions.
Keywords: Nanoparticle; Colloidal Solution; Phase Transition; Gold; Physics, Condensed Matter (0611)